The role of technology adoption in the relationship between MAP and MSMEs financial performance based on the resource-based view theory - Bani Alkausar; Soemarsono, Prinintha Nanda; Wulandari, Annisa; Pangesti, Nitami Galih; Pertiwi, Ajeng Rachma (Journal of Multiperspectives on Accounting Literature, 2025)
Purpose: This study aims to explore the implementation of Management Accounting Practice (MAP) and the business performance of MSMEs, as well as the role of technological advancements and external support as enabling factors to enhance MSMEs business performance. Methodology/approach: This study employs a quantitative approach using a survey-based research instrument. Primary data were collected through a questionnaire designed based on indicators of Management Accounting Practices, business performance, and other relevant factors affecting MSMEs. The data were analyzed using structural equation modeling (SEM). Findings: The result show that management accounting practices function more as internal information systems supporting decision-making, but their impact on performance outcomes requires mediating factors such as technology and innovation. This implies that improving the quality of MAP must be accompanied by strategies for actively utilizing information in business transformation processes. Practical implications: This study provides a foundation for MSMEs practitioners, business consultants, and policymakers to not only focus on strengthening financial administration but also to encourage the integration of management accounting practices with digital technology and innovation as part of a sustainable business growth strategy. Originality/value: This study attempts to address the gap in empirical research that examines the mediating role of technology adoption and e-business innovation in the relationship between management accounting practices and MSMEs performance, particularly in developing countries such as Indonesia.